2019
DOI: 10.3390/s19204388
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Daily-Life Gait: Novel Outcome for Trials that Focus on Balance, Mobility, and Falls

Abstract: Technological advances in inertial sensors allow for monitoring of daily-life gait characteristics as a proxy for fall risk. The quality of daily-life gait could serve as a valuable outcome for intervention trials, but the uptake of these measures relies on their power to detect relevant changes in fall risk. We collected daily-life gait characteristics in 163 older people (aged 77.5 ± 7.5, 107) over two measurement weeks that were two weeks apart. We present variance estimates of daily-life gait characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
17
2
Order By: Relevance
“…Our aim was to examine the association between gait quality characteristics with the severity of physiological fall risk in community-dwelling older people. These gait quality characteristics were previously validated on falls but analyses were performed in the same cohort (FARAO cohort, 319 older people aged 65–99 years) [ 4 , 5 , 6 , 7 , 14 ]. In line with the previous validation on falls [ 5 ], our results indicated that logarithmic rate of divergence per stride in VT and AP were associated with physiological fall risk while sample entropy and a gait quality composite score were, against our expectations, not associated with physiological fall risk after adjusting for walking speed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our aim was to examine the association between gait quality characteristics with the severity of physiological fall risk in community-dwelling older people. These gait quality characteristics were previously validated on falls but analyses were performed in the same cohort (FARAO cohort, 319 older people aged 65–99 years) [ 4 , 5 , 6 , 7 , 14 ]. In line with the previous validation on falls [ 5 ], our results indicated that logarithmic rate of divergence per stride in VT and AP were associated with physiological fall risk while sample entropy and a gait quality composite score were, against our expectations, not associated with physiological fall risk after adjusting for walking speed.…”
Section: Discussionmentioning
confidence: 99%
“…For every gait quality characteristic, we took the median of all epochs over one week as a representation of someone’s daily life gait quality [ 4 , 5 , 7 ]. In total, we extracted walking speed and six gait characteristics: sample entropy in ML and VT, logarithmic rate of divergence in VT, ML and AP and the gait quality composite [ 5 , 14 ]. Walking speed was determined from the product of stride frequency and stride length, estimated from leg length and vertical trunk displacements assuming compass gait [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical gait analysis is designed to reveal the key links and influencing factors of gait anomalies through biomechanics and kinematics, to help evaluate and treat through rehabilitation, and to help to assist clinical diagnosis, curative effect evaluation, and pathological research, etc. [5,6]. An effective gait analysis is usually performed in clinical or research settings and quantitatively measures the exact angles of the knees, ankles, and hips when walking or running.…”
Section: Introductionmentioning
confidence: 99%